2016
DOI: 10.1016/j.jhydrol.2016.03.018
|View full text |Cite
|
Sign up to set email alerts
|

Patterns of temporal scaling of groundwater level fluctuation

Abstract: SUMMARY We studied the fractal scaling behavior of groundwater level fluctuation for various types of aquifers in Puerto Rico using the methods of (1) detrended fluctuation analysis (DFA) to examine the monofractality and (2) wavelet transform maximum modulus (WTMM) to analyze the multifractality. The DFA results show that fractals exist in groundwater fluctuations of all the aquifers with scaling patterns that are anti-persistent (1 < β < 1.5; 1.32 ± 0.12, 18 wells) or persistent (β > 1.5; 1.62 ± 0.07, 4 well… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
29
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 27 publications
(34 citation statements)
references
References 47 publications
1
29
0
Order By: Relevance
“…They analyzed 4 years of continuous hourly data from seven wells and found that groundwater level fluctuations are likely to follow fractional Brownian motion (fBm) and that temporal scaling crossovers exist in the fluctuations. These findings were later confirmed by Little and Bloomfield (2010), Rakhshandehroo and Amiri (2012), and Yu et al (2016) with the application of DFA to hourly or 15 min interval data for up to 5 years from 7 wells, daily data for 6 years from 2 wells, and daily data from 22 wells that have more than 2500 records, respectively. Rakhshandehroo and Amiri (2012) further utilized MF-DFA to evaluate the multifractality of groundwater level fluctuations and concluded that the extent of multifractality in groundwater level fluctuations is stronger than that in river runoff.…”
mentioning
confidence: 71%
See 4 more Smart Citations
“…They analyzed 4 years of continuous hourly data from seven wells and found that groundwater level fluctuations are likely to follow fractional Brownian motion (fBm) and that temporal scaling crossovers exist in the fluctuations. These findings were later confirmed by Little and Bloomfield (2010), Rakhshandehroo and Amiri (2012), and Yu et al (2016) with the application of DFA to hourly or 15 min interval data for up to 5 years from 7 wells, daily data for 6 years from 2 wells, and daily data from 22 wells that have more than 2500 records, respectively. Rakhshandehroo and Amiri (2012) further utilized MF-DFA to evaluate the multifractality of groundwater level fluctuations and concluded that the extent of multifractality in groundwater level fluctuations is stronger than that in river runoff.…”
mentioning
confidence: 71%
“…Consequently, groundwater level fluctuations are often nonstationary, rendering variabilities over different spatial and temporal scales and resulting in no dependence on single representative spatial and temporal scales. Therefore, groundwater level fluctuations are often characterized as scale-free processes and modeled as fractional Brownian motion (Hardstone et al, 2012;Yu et al, 2016). Although not necessarily totally random, groundwater level fluctuations may demonstrate long-range dependence through time, implying…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations